THE SOUTH CHINA SEA GEOPOLITICAL DYNAMICS AND INDONESIA'S MARITIME SECURITY: A POLITICAL DEFENSE ANALYSIS - Ras, Abdul Rivai (Universitas Padjadjaran, 2024)
This study aims to analyze the geopolitical dynamics in the South China Sea (SCS) region in relation to Indonesia's maritime security, viewed from the perspective of defense politics. The geopolitical dynamics in the SCS region are driven by China's claims through its Nine-Dash Line (NDL). China, as described by Cohen's Four Pillars (2015) as a country with extraordinary military power, has factually been willing to use it to legitimize and defend its claims. The surplus of economic power, besides being spent on modernizing its defense forces, is then utilized in the form of investment through the Belt and Road Initiative (BRI) policy. These two pillars have become China's strength to dominate the SCS region. This study concludes that Indonesia needs to develop a defense political strategy as a soft power to face the major challenges of geopolitical dynamics in the SCS region. This defense politics can optimize ASEAN as first-track diplomacy and other activities as second-track diplomacy.